SUBACUTE TREATMENT OF COPAIBA AND WHITE ROSIN ESSENTIAL OILS USING INTEGRATED BIOMARKER RESPONSES ON THE REPRODUCTIVE SYSTEM OF WISTAR RATS EXPOSED TO VALPROIC ACID - Britto, Diana e Britto; Dias, Fernanda; Guimarães, Pollyana; Silva, Randerson; Silva, Anderson; Alves, Luiz; Brayner , Fábio; Silva-junior, Valdemiro (Acta Biologica Brasiliensia, 2025)
Valproic acid (VPA) is a short-chain fatty acid used as a treatment for epilepsy, in both adults and children. Treatment with valproic acid presents several side effects, such as male subfertility, causing reversible changes in sperm motility, morphology, sperm count, and testicular cytoarchitecture. The objective was to understand how the use of valproic acid during pregnancy can affect the fertility of male offspring, and whether the use of copaiba, white breu essential oils, or their combination can reverse the damage caused. Female rats in the negative control group received water, while those in the experimental groups received valproic acid (600 mg/kg) intraperitoneally, in a single dose. The male offspring were divided into six groups: negative and positive controls, vehicle, treated with copaiba oil, white breu oil, and a combination of copaiba and white breu oils. The TERRA® oils were administered via gavage for 30 consecutive days. Results showed oxidative and nitrosative stress in the testis and epididymis, along with alterations in antioxidant enzyme activity. Mild testicular changes and cribiform areas in the epididymis were observed. It was concluded that exposure to valproic acid during the intrauterine period causes oxidative damage and structural alterations in both the testis and epididymis. However, the use of essential oils at this dose and duration was not sufficient to reverse these damages, even though it altered the activity of antioxidant enzymes.